El Materialismo dialéctico, como lógica y praxis pedagógica en la educación - Mejía Pacheco, Ángel David (2015)
The dialectical materialism like logical and pedagogical praxis in the education looks for fathoming the ontological bases in which the capitalist system is founded. When we use the dialectical method we discover different ways to manipulate the concept of educational quality, and the actual way to promote that concept to educators and learners. Unwillingly the educators support the system into the classrooms and in each educational practice. The capitalist system makes ephemeral needs based in to have and produce weaving an ontological tie between students’ being, knowing and acting. From this optics the dialectical materialism with the logical and the praxis which are discovered in a conciliatory role and otherwise the sake of seeking substantial value of education, proposing aside from traditional knowledge and outdated in which sense the curricula is based, to will generate a reflexive and critical education, attached to solve the social problems of the students into the educational institutions, and this way to forge an authentic human being. An authentic human is always forged and when capitalists terms coined in the educational system such as: competency assessment, skills, quality standards and educational quality these lead to generate in the students a sense of injustice and despair about economic hardship of the people, reflected in desperation to get fast and effective results, they are the chains that prevent the construction of a fair, fraternal and free society.